Does Institutional Ownership and Bank Monitoring Affect Agency Conflicts? Evidence from an Emerging Market - Bagus Dwi Ariyono; Bowo Setiyono (Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
Introduction/Main Objectives: This study examines the effect of institutional ownership, proxied by government and private ownership, and bank monitoring on agency conflicts. Background Problems: The previous literature focused on agency conflicts, particularly those between managers and shareholders in developed markets, with much less evidence being presented from emerging ones. Novelty: We consider the role of creditors (the banks) in mitigating agency conflicts, and the managers’ irresponsible behavior, which in previous studies has been largely under-elaborated. Research Methods: Using 1,525 observations of 305 non-financial companies that were listed in the 2011-2015 period, we employ the generalized least squares method to deal with potential econometric concern such as autocorrelation and heteroscedasticity. Finding/Results: We find that institutional ownership and bank monitoring, proxied by the number of banks and the share of their loans, are negatively related to agency conflicts. Conclusion: Banks and institutional ownership lead to lower agency conflicts. However, one should mitigate free-rider problems emanated from these relationships.